2018
DOI: 10.1038/s41366-018-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing, circulating exosomes, and insulin sensitivity in adipocytes

Abstract: BackgroundSleep-disordered-breathing (SDB), which is characterized by chronic intermittent hypoxia (IH) and sleep fragmentation (SF), is a prevalent condition that promotes metabolic dysfunction, particularly among patients suffering from obstructive hypoventilation syndrome (OHS). Exosomes are generated ubiquitously, are readily present in the circulation, and their cargo may exert substantial functional cellular alterations in both physiological and pathological conditions. However, the effects of plasma exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 72 publications
1
52
0
Order By: Relevance
“…OSA is particularly present among obese individuals and can affect at least 4–10% of all adults, with recent epidemiological studies reporting much higher prevalence [ 6 , 7 , 8 ]. Patients with OSA are at greater risk for metabolic dysfunction including insulin resistance, type 2 diabetes mellitus, dyslipidemia, and display evidence of adipose tissue inflammation and dysfunction [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Of note, both IH and SF have been independently associated with metabolic dysfunction, and acute exposures to IH were shown to decrease insulin sensitivity in healthy human volunteers [ 16 , 17 ].…”
Section: Sleep-disordered Breathingmentioning
confidence: 99%
“…OSA is particularly present among obese individuals and can affect at least 4–10% of all adults, with recent epidemiological studies reporting much higher prevalence [ 6 , 7 , 8 ]. Patients with OSA are at greater risk for metabolic dysfunction including insulin resistance, type 2 diabetes mellitus, dyslipidemia, and display evidence of adipose tissue inflammation and dysfunction [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Of note, both IH and SF have been independently associated with metabolic dysfunction, and acute exposures to IH were shown to decrease insulin sensitivity in healthy human volunteers [ 16 , 17 ].…”
Section: Sleep-disordered Breathingmentioning
confidence: 99%
“…A sub-analysis of the HIPARCO clinical trial [37] revealed that a panel of miRNAs could be used to reliably predict which patients with refractory hypertension and OSA would respond better to CPAP therapy in terms of reducing their blood pressure. An experiment conducted by Khalyfa et al [45] found a possible pathophysiological relationship among the circulating miR-NAs of obese patients with OSA, adipocyte alterations, and the mechanisms of insulin resistance [45].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma EVs isolation and characterization from blood samples were performed using a previously described protocol that enriches for exosomes [6,42]. Indeed, negative stain electron microscopy showed vesicles in typical shaped morphology ( Figure 2A) [32,38,43], and as shown in Figure 2B, unique exosome markers were used to conclusively identify EVs using flow cytometry of isolated EVs derived from CO, OSA-NC(−), or OSA-NC(+). As shown in Figure 2B, each image was stained separately with a different antibody using two different negative controls (all reagents without antibody and no EVs (negative #1), all reagents without EVs (negative #2)).…”
Section: Evs Characterization and Quantificationmentioning
confidence: 99%
“…EVs were quantified using enzymatic fluorescent assay (FluoroCet #FCET96A quantitation kit; System Biosciences, Mountain View, CA, USA) according to the manufacturer's protocols [32]. The assay was used to measure the esterase activity of cholesteryl ester transfer protein (CETP) activity, and the standard curve was calibrated to known EVs counts.…”
Section: Evs Characterization and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation